2018
DOI: 10.1007/s10916-018-1000-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Interest and Economic Impact of Preoperative SMS Reminders before Ambulatory Surgery: A Propensity Score Analysis

Abstract: Patient contact by telephone the day before ambulatory surgery is considered as a best practice. The Short Message Service (SMS) could be a suitable alternative. The objective of this prospective study was to evaluate the interest of preoperative instruction (PI) reminders by SMS compared to telephone calls. This was a prospective single center before-and-after study. Patients scheduled in ambulatory surgery were included during 2 consecutive periods of 10 weeks. The "Call" group received a telephone call for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…First, the use of an SMS reminder before day surgery may be an efficient tool to confirm oral information given during a preanesthesia consultation. Garnier et al [ 14 ] showed that the use of SMS reminders significantly increased compliance with preoperative instructions, time of arrival, fasting rules, and hygiene rules. In our work, this decrease was associated with anesthetic causes, defined by persisting pain, postoperative nausea and vomiting, sickness, and aspiration syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the use of an SMS reminder before day surgery may be an efficient tool to confirm oral information given during a preanesthesia consultation. Garnier et al [ 14 ] showed that the use of SMS reminders significantly increased compliance with preoperative instructions, time of arrival, fasting rules, and hygiene rules. In our work, this decrease was associated with anesthetic causes, defined by persisting pain, postoperative nausea and vomiting, sickness, and aspiration syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently used indicator is the conversion rate to full-time hospitalization [ 10 - 13 ]. Previous studies have shown that the use of SMS reminders before outpatient surgery increased the rates of compliance with preoperative instructions [ 14 ] and reduced the number of cancellations in gastrointestinal endoscopy [ 15 ]. The objective of this study was to evaluate the impact of pre- and postoperative SMS messages on medical safety in outpatient surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In another study [ 5 ], SMS text message reminders and a smartphone app were used successfully to monitor and reduce the alcohol consumption of military veterans—from a median of 5.6 units per drinking day in the first week to 4.7 units by the last week during the 4 weeks of study. For outpatient surgery, previous studies have shown that the use of SMS text message reminders before the surgery increased the rates of compliance with preoperative instructions [ 6 ], reduced the number of cancellations in gastrointestinal endoscopy [ 7 ], and decreased the rate of conversion to full-time hospitalization [ 8 ]. SMS text messaging might be an interesting alternative to follow patients at home during the postoperative period.…”
Section: Introductionmentioning
confidence: 99%
“…[ 43 ] However, DOS cancellations due to patients’ lack of compliance to preoperative instructions have decreased but are still happening. [ 43 , 8 ]…”
Section: Introductionmentioning
confidence: 99%